Hope and Psychological Energy among Patients with Chronic Diseases: Correlation and Comparative Study - Meiri, Elwaleed Abdalla Farih; Al Zahrani, Bandar Alalam; Refai , Aza Mohamed Sediek; Hakami, Ibrahim bin Qasem (Journal of Ecohumanism, 2024)
The present study aims to identify the correlation between hope and psychological energy in patients with chronic diseases. The study consists of a sample of 100 patients with chronic diseases (diabetes, blood pressure, gastric ulcers, irritable bowel syndrome, and asthma-adipose) residing in Riyadh, Saudi Arabia. The study adopted the relational descriptive approach and used two scales, namely the hope scale of Snyder et al. (1991) and the psychological energy scale of Zaidan (2003). Data was entered and analyzed by the SPSS-22 statistical program. The results of the study concluded that there was a statistically significant correlation between hope and psychological energy in patients with chronic diseases. The results also confirmed the alternative hypothesis that there are significant differences in hope by sex and duration of disease. Differences were also significant in psychological energy according to the duration of the disease. The study concluded that hope and psychological energy are protective factors that allow the individual to cope with difficult and painful experiences, including chronic or dangerous diseases.